Integrated Analysis of FAM57A Expression and Its Potential Roles in Hepatocellular Carcinoma - Wei, Junwei; Liu, Yun; Zhao, Caiyan (Frontiers in Oncology, 2021)
Background Family with sequence similarity 57 member A (FAM57A) is a membrane associated gene contributing to lung carcinogenesis. In hepatocellular carcinoma (HCC) and other cancers, whether FAM57A exerts similar roles has been rarely reported. Herein, the biological functions and clinical significance of FAM57A in HCC were explored. Methods Initially the differential expression of FAM57A between nontumor and HCC tissues was validated using a number of publicly accessible databases and immunohistochemistry (IHC). Then, the Kruskal–Wallis rank sum test or the Wilcoxon rank sum test as well as logistic regression were employed to analyze the association of FAM57A expression with clinical characteristics of HCC. The Cox regression and Kaplan–Meier analyses were conducted to assess the prognostic significance. Besides, with the coexpression analysis, Gene Ontology (GO), Gene Set Enrichment Analysis (GSEA), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, the molecular pathomechanisms that were mediated by FAM57A in HCC were elucidated. Furthermore, the correlations between FAM57A expression and tumor-infiltrating immune cells (TIICs) or immune checkpoint genes were analyzed. Finally, in vitro cell functional assay was carried out to preliminarily verify the role of FAM57A in HCC. Results FAM57A expression was demonstrated to be higher in HCC samples than in nontumor samples (all p-values <0.05), statistically correlated with clinicopathological characteristics (clinical stage, T stage, pathological grade), and inversely correlated to HCC patient survival. Univariate and multivariate Cox regression analyses showed that FAM57A expression could independently predict prognosis in HCC patients. Functional enrichment analyses further indicated that FAM57A was involved in multiple tumor-related pathways. FAM57A expression was positively correlated with TIICs, gene markers of TIICs, as well as immune checkpoint genes. Also, high expression of FAM57A predicted a poor prognosis for HCC based on immune cell subgroups. Functional assay of FAM57A knockdown significantly inhibited cell proliferation and induced cell apoptosis in HCC cells. Conclusions Our results indicated that FAM57A could be used as a biomarker to predict the prognosis and immunotherapy response for HCC patients and might function as an oncogene to promote HCC progression.